Efeitos do consumo de ácidos graxos n-3, n-6 e trans sobre aspectos bioquímicos e moleculares em um modelo animal de mania - Trevizol, Fabíola (2014)
Fatty acids (FA) are constituents of neuronal phospholipid membranes, where they are essential for the development and functioning of the brain. During the peak of neuronal growth, occurring during the last week of gestation and lactation, there is a rapid accumulation of long-chain polyunsaturated FA (LC-PUFAs), which are synthesized from a physiologically appropriate supply of essential fatty acids (EFA) for normal fetal and neonatal development , ensuring the development of neurological functions. During the last decades, there occurred changes in dietary habits in Western countries, mainly with increased consumption of trans fatty acids (TFA) and omega-6 (n-6) at the expense of consumption of omega-3 (n-3). These changes may increase oxidative damage and alter neuronal neuroplasticity, thereby facilitating the development of neuropsychiatric diseases such as bipolar disorder (BD). Through a model of amphetamine-induced mania in rats, we evaluated comparatively the influence of daily supplementation of different fats since pre-conception until weaning of 1st and 2nd generation litters on behavioral parameters in conjunction with biochemical changes in brain regions. Three groups of female Wistar rats were supplemented (3g/kg; p.o. per day) from one week before conception through pregnancy and breast-feeding with fish oil (FO, rich in n-3 PUFA), soybean oil (SO; rich in PUFA n-6) or hydrogenated vegetable fat (HVF; rich in TFA). During weaning, pups of both sexes were kept under the original supplementation until 90 days of age. While male offspring were included in the study of the 1st generation, females were mated and maintained in the same supplementation, thus obtaining animals of the 2nd generation, which were used in the 2nd study and divided into 3 experiments. In the study of the 1st generation at 90 days of age, one half of each supplementation group was treated with a daily dose of amphetamine (AMPH 4mg/kg, ip) or saline (control) for 14 days, when they were subjected to behavioral tests and biochemical assessments in the cortex, striatum and hippocampus. HVF supplementation was associated with TFA incorporation in the three structures, increased AMPH-induced locomotor activity, and increased oxidative damage. Since FO supplementation increased DHA percentage and decreased the n6/n3 ratio in the three regions analyzed, it may have improved membrane fluidity and reduced oxidative stress in such animals. Adult male rats born from the 2nd generation were also exposed to an animal model of mania induced by amphetamine and used in two different experiments. In the first experiment, animals were evaluated for memory behavior and biochemical and molecular analysis in the hippocampus, in which these parameters were decreased by HVF supplementation and improved by FO supplementation. In the second experiment, animals were evaluated regarding hyperactivity and biochemical and molecular analyses in the cortex, where again HVF supplementation was associated with loss in some parameters. In a third experiment we evaluated the influence of trans fat supplementation in rats exposed to the same mania animal model and the response to lithium (a mood stabilizing drug) treatment in 1st and 2nd generation animals. Lithium was able to reverse all AMPH-induced effects. Taken together, our findings suggest that the increased consumption of processed foods, which are rich in trans fat, may be related to an increased incidence of neuropsychiatric conditions. Conversely, a balanced diet, which includes omega-3 sources , reduces susceptibility to developing such conditions, possibly by changing the composition of the neuronal phospholipid membrane.